Analisi Kesiapan Guru dalam Mengimplementasikan Kurikulum Merdeka Disekolah Dasar di SDN 060812 Medan Area - Engelina Nababan; Kholijah Saprayani; Siti Mutia; Siti Syahira; Sri Menda Cristina Br Ginting; Asiah Ramadani; Lala Jelita Ananda (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This research is a case study with the subject of research Mrs. Sarah Syafrayani, S.Pd As a homeroom teacher of class V at SDN Negeri 060816, Sukamai, Medan Area District, Medan City, a descriptive research type with a qualitative approach. In accordance with Mukhtar's statement (2013), this type of research describes the conditions that are in accordance with the objects observed and then the data obtained is written in the form of a report. The results of the interview showed that not all teachers have the same understanding of the Independent Curriculum. Some teachers understand the basic concepts of this curriculum, such as flexibility in compiling learning and an emphasis on project-based learning. However, some others are still confused about translating the principles of the Independent Curriculum into classroom learning practices. The main obstacle in understanding this curriculum is the lack of socialization and training provided to teachers. Many teachers feel that they have not received sufficient technical guidance regarding the preparation of teaching modules, learning objective flows (ATP), and assessment strategies that are in accordance with this curriculum. Some teachers also stated that the change from the previous curriculum to the Independent Curriculum happened too quickly, so they did not have enough time to adapt. This is in line with research by Indriastuti et al. (2017), which states that flexibility in learning can increase students' learning motivation and strengthen their involvement in the learning process. However, despite having a positive view of this curriculum, teachers still hope for further support from the government and schools in the form of training, provision of facilities and infrastructure, and technical guidance related to the implementation of this curriculum.